2017
DOI: 10.1111/1556-4029.13458
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Methamphetamine in Mouse Thighbones Buried in Soil

Abstract: Bone samples are used for analysis of drugs in decomposed or skeletonized bodies. Toxicological analyses of buried bones are important for determining the causes and circumstances of death. In this study, methamphetamine and amphetamine concentrations in heart blood, thigh muscles, and thighbones were analyzed using solid-phase extraction with liquid chromatography-tandem mass spectrometry. Methamphetamine concentrations in heart blood, thigh muscle, and thighbone ranged from 0.041 to 0.873 μg/mL, 0.649 to 2.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this study, amphetamine had lower accuracy, recovery rate, and matrix effect values than methamphetamine. In our previously reported study, only the amphetamine recovery rate was low when the bone was used as the matrix [8]. The extraction operation was the same as in the present study.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In this study, amphetamine had lower accuracy, recovery rate, and matrix effect values than methamphetamine. In our previously reported study, only the amphetamine recovery rate was low when the bone was used as the matrix [8]. The extraction operation was the same as in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have examined drug concentrations in bones and have shown that they tend to be higher in bones than in blood [8,9,11,23]. One reason why drugs can be present in the bone is due to structural factors.…”
Section: Ta B L E 2 Intra-and Interday Precisionmentioning
confidence: 99%
See 3 more Smart Citations